Valaciclovir compared with acyclovir for improved therapy for herpes zoster in immunocompetent adults - Karl R. Beutner; Daniel Friedman; Chistine Forszpaniak; Paul Andersen; Marsha Wood (1995)
Acyclovir treatment of acute herpes zoster speeds rash healing and decreases pain and ocular complications. The limited oral bioavailability of acyclovir necessitates frequent dosing. Valaciclovir, the l-valyl ester of acyclovir, is rapidly and almost completely converted to acyclovir in vivo and gives three- to fivefold increases in acyclovir bioavailability. In a randomized, double-blind, multicenter study, the safety and efficacy of oral valaciclovir given at a dosage of 1,000 mg three times daily for 7 or 14 days and oral acyclovir given at a dosage of 800 mg five times daily for 7 days were compared in immunocompetent adults aged > or = 50 years with herpes zoster. Patients were evaluated for 6 months. The intent-to-treat analysis (1,141 patients) showed that valaciclovir for 7 or 14 days significantly accelerated the resolution of herpes zoster-associated pain (P = 0.001 and P = 0.03, respectively) compared with acyclovir; median pain durations were 38 and 44 days, respectively, versus 51 days for acyclovir. Treatment with valaciclovir also significantly reduced the duration of postherpetic neuralgia and decreased the proportion of patients with pain persisting for 6 months (19.3 versus 25.7%). However, there were no differences between treatments in pain intensity or quality-of-life measures. Cutaneous manifestations resolved at similar rates in all groups. Adverse events were similar in nature and prevalence among groups, and no clinically important changes occurred in hematology or clinical chemistry parameters. Thus, in the management of immunocompetent patients > or = 50 years of age with localized herpes zoster, valaciclovir given at 1,000 mg three times daily for 7 days accelerates the resolution of pain and offers simpler dosing, while it maintains the favorable safety profile of acyclovir.